Gejala Depresi pada Remaja Korban Bullying: A Scoping Review - Muhammad Yusuf Anshori; Azzam David Saifullah; Ayyu Sandhi (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2022)
Background: Depression is of major causes for disease and disability in adolescents. One of many factors that make teenager more vulnerable to depression is bullying. Identification of depression symptoms among adolescent is important to be investigated, especially due to bullying.Objective: To review the symptoms of depression in adolescents caused by bullying.Method: This is a scoping review research. Databases used were PubMed, EBSCOhost, Cochrane, and PsycNET. Inclusion criteria were: English and Bahasa Indonesia literature, published from 2013 to 2018, quantitative and/or qualitative research adolescent who suffered from depression due to bullying as the research subject, and available free full text. The article screening was based on PRISMA guidance; articles were assessed with the Crowe Critical Appraisal Tool (CCAT), extraction was done on Google form, and synthesis was performed on the extraction resultResults: 19 articles were obtained from the literature screening. Signs and symptoms of depression due to bullying were divided into three groups: psychic symptoms, physical symptoms, and social symptoms. A common symptom of depression in adolescents suffered from bullying was the desire for death, and the desire for death became the most general signs and symptoms of the adolescents who became bullying victims.Conclusions: Being a victim of bullying may cause adolescents to suffer from symptoms of depression in the form of psychic symptoms, physical symptoms, and social symptoms.ABSTRAKLatar belakang: Depresi merupakan pemicu penyakit hingga kecacatan pada usia remaja. Salah satu faktor yang menjadikan usia remaja rentan mengalami depresi adalah bullying. Identifikasi gejala depresi pada remaja penting untuk dipelajari, terutama akibat bullying.Tujuan: Melakukan review gejala-gejala depresi pada remaja korban bullying.Metode: Penelitian ini merupakan scoping review, artikel diperoleh dari proses pencarian pada database PubMed, EBSCOhost, Cochrane, dan PsycNET. Kriteria inklusi artikel yaitu literatur berbahasa Inggris dan bahasa Indonesia, terbit dari tahun 2013-2018, penelitian kuantitatif dan/atau kualitatif dengan populasi penelitian berupa remaja korban bullying, serta artikel penuhnya dapat diakses. Skrining bertahap dilakukan dan didokumentasikan sesuai bagan alir PRISMA. Artikel hasil skrining dinilai dengan Crowe Critical Appraisal Tool (CCAT), ekstraksi dan sintesis artikel dilakukan pada Google Form.Hasil: Dalam proses screening, diperoleh 19 artikel. Gejala depresi pada remaja korban bullying dapat dikelompokkan menjadi tiga yaitu gejala psikis, gejala fisik, dan gejala sosial. Gejala khas depresi pada remaja korban bullying adalah gejala psikis berupa ide bunuh diri. Ide bunuh diri ini menjadi tanda dan gejala depresi yang paling banyak ditemukan pada remaja korban bullying.Kesimpulan: Kejadian bullying selama masa remaja berpengaruh secara potensial untuk menyebabkan gejala depresi baik gejala psikis, gejala fisik, maupun gejala sosial.